Improving Junior High School Students’ Vocabulary in Descriptive Reading Using Quizizz E-Flashcards - Nirmala Aji (Retain: Journal of Research in English Language Teaching, 2026)
Vocabulary, specifically in reading, is a skill that needs to be mastered by EFL students (Yüksel et al., 2022) due to rapid development of technology that affects language learning process. However, vocabulary skills of Indonesian students are still concerning due to several reasons: (1) demotivated in learning English (2) addicted to gadget (3) preferred an instant result. Thus, the researcher attempted to overcome the problem by using e flashcards to enhance students’ vocabulary. The participants of this research were 8th grader from one of junior high schools in Surabaya that is chosen based on purposive sampling. Moreover, they were divided into experimental group (N=30) and control group (N=30) since this research used quasi-experimental as the research design. Furthermore, the participants were assigned to do the pre-test that contains 15 items of vocabulary before receiving the treatment for 3rd times. The test was adapted from Updated Vocabulary Levels Test developed by (Webb et al., 2017). A day later after the last treatment given, they were asked to do the post test that had the exact content as the pre-test, but the order of the questions was shuffled. The findings of this research showed that the treatment, which is the e-flashcards, had a small effect (0.01) on students’ vocabulary improvement (Kornell & Bjork, 2008; Uchihara et al., 2019). Nevertheless, according to the mean difference of pre-test and post-test score, experimental group (M=3.33) outperformed the control group (M=1.27). In other words, e-flashcards can be an alternative media to enhance students’ word attainment with more development for better results.